2023
DOI: 10.1037/fam0001114
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of perceived family reactions to youth LGBTQ identity.

Abstract: Family members’ reactions to youth identity disclosure are important predictors of well-being for lesbian, gay, bisexual, transgender, queer, or questioning (LGBTQ) youth. To better understand potential variation within and across families’ current reactions, this study established latent profiles of family level reaction patterns and examined predictors and outcomes associated with these patterns. In 2011–2012, LGBTQ youth (N = 447, Mage = 18.8) rated their mother’s, father’s, brother’s, and sister’s reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some samples have found that nonbinary individuals disclose their identities at later ages than transgender individuals (Scandurra et al, 2021) and that bisexual individuals disclose their identities later than individuals with emerging sexual identities (Bishop et al, 2020). A recent latent class analysis also found that transgender youth were more likely to receive negative reactions from family members in response to disclosing their identity compared to cisgender sexual minority youth (McCurdy et al, 2023). As such, being outed likely unfolds differently between SGDY.…”
Section: Sexual and Gender Identity Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Some samples have found that nonbinary individuals disclose their identities at later ages than transgender individuals (Scandurra et al, 2021) and that bisexual individuals disclose their identities later than individuals with emerging sexual identities (Bishop et al, 2020). A recent latent class analysis also found that transgender youth were more likely to receive negative reactions from family members in response to disclosing their identity compared to cisgender sexual minority youth (McCurdy et al, 2023). As such, being outed likely unfolds differently between SGDY.…”
Section: Sexual and Gender Identity Disclosurementioning
confidence: 99%
“…The relation between the stress of being outed to parents and LGBTQ family support is likely to vary across sexual and gender identities. For instance, SGDY who identify as transgender, nonbinary, bisexual, pansexual, queer, or asexual may exhibit greater stress after learning their identities have been outed to their parents, which may manifest through greater perceptions of parental rejection or invalidation of their identities (e.g., Simon et al, 2022;McCurdy et al, 2023; for a review, see Wittlin et al, 2023). Consequently, the indirect association of outed stress to parents and depressive symptoms through LGBTQ family support may be stronger for SGDY who identify with non-cisgender and emerging sexual identities (e.g., pansexual or queer).…”
Section: Depressive Symptoms and Parental Support Among Sgdymentioning
confidence: 99%